Development of a Model for Individual Educational Pathways in Engineering Education - Nikolay I. Naumkin; Vadim A. Ageev; Anarkul E. Sadieva; Anatoly V. Anokhin; Natalya N. Shekshaeva; Evgeniya V. Zabrodina (National Research Mordova State University, 2021)
Introduction. Individual educational pathways are widely used in higher education to optimize the educational process and harmonize the personal needs of students. The problem of their further development consists in improving scientific and methodological support and meeting the requirements of documents regulating educational activities. The purpose of the article is to present the results of theoretical substantiation, development and implementation of a model for individual educational pathways in engineering education. Materials and Methods. As a research toolkit, a methodological system, including an integrated and interdisciplinary (combine all components of the model of individual educational trajectories into a system), systemic, substrate and structured (for designing new models of individual educational trajectories) approaches was used; hypothetical-deductive, analysis-synthesis, morphology and classification (to analyze all possible models of individual educational trajectories), modeling and design (to create various individual educational trajectories) methods were also utilized. Results. In the course of the study, the definition of an individual educational pathway was formulated. As a result of the joint work of the authors from Mordovia State University and the engineering universities of the Republic of Kyrgyzstan, individual educational trajectories were developed for students of engineering specialisms at these universities. A generalized combinatorial model of possible individual educational pathways of engineering specialism has been developed. Discussion and Сonclusion. The results obtained contribute to the development of the curriculum design theory in the context of individual educational pathways. The materials of the article will be useful to researchers dealing with the problems of personalization of learning based on the use of individual educational trajectories.